Step 4 assessment of the promotion for breastfeeding in baby-friendly hospital - Monte, Giselle Carlos Santos Brandão; Leal, Luciana Pedrosa; Pontes, Cleide Maria (Rev Rene, 2012)
The objective of this study was to evaluate the implementation of the 4th step to promote maternal breast-feeding in a child-friendly hospital in Recife, PE, Brazil. It is a descriptive, observational, transversal and quantitative study. The sample covered 80 health professionals, of which 47 were doctors and 33 from the nursing team. The data collected through interviews and non-participative observation was analysed by the Epi-Info version 6.04 program, undergoing descriptive and bivariate analysis, using the chi-square test, considering a significance level of 5%. Only 36.6% of newborns reached the 4th step. Among those with an Apgar ≥ 6 in the 1st minute, 59.3% were neither placed on the breast nor had skin contact with their mother. Transvaginal delivery was statistically more significant in comparison to caesarean. The hospital in the study is not implementing the 4th step for promoting breast-feeding as routine.